2011
DOI: 10.1016/j.ejsobi.2011.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Resilience of soil microbial communities impacted by severe drought and high temperature in the context of Mediterranean heat waves

Abstract: International audienceIn the context of Climate Change, the increasing of frequency and intensity of droughts and heat waves constitutes a serious threat for agroecosystems in the Mediterranean region. Soils and their functions may be impacted by these extreme events through changes in the biomass, composition and activities of edaphic microbial communities. We designed an experiment to investigate changes over time in the microbial biomass, composition (EL-FAME profiles) and functions (catabolic responses) af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(62 citation statements)
references
References 43 publications
2
59
1
Order By: Relevance
“…These results are in agreement with those obtained by Bérard et al . (), who observed that after 21 days of drought the Gram+ population had not changed with regard the soil that had not been subjected to drought, possibly because they have more rigid cell walls, making them more resistant to drying processes (Uhlirova et al ., ).…”
Section: Discussionmentioning
confidence: 98%
“…These results are in agreement with those obtained by Bérard et al . (), who observed that after 21 days of drought the Gram+ population had not changed with regard the soil that had not been subjected to drought, possibly because they have more rigid cell walls, making them more resistant to drying processes (Uhlirova et al ., ).…”
Section: Discussionmentioning
confidence: 98%
“…This enabled us to assess the catabolic diversity of the soil and microbial biomass via measurements SIR glucose (Anderson & Domsch ). The metabolic quotient qCO 2 was calculated as the ratio of BR to SIR glucose (Chapman et al ; Bérard et al ) to determine how efficiently microorganisms use available carbon in soil (Anderson & Domsch ). This quotient is considered a microbial eco‐physiological indicator.…”
Section: Methodsmentioning
confidence: 99%
“…Another source of enzymes that may have supported the relatively high EAs we reported during peak drought may be via the release of enzymes upon cell death (Berard et al, 2011). Although the efficiency of extracellular enzymes increases with temperature (Koch et al, 2007), low moisture availability would likely limit enzyme and substrate diffusion (Allison, 2005;Bell et al, 2010).…”
Section: Comparison Of Soil Eas During and After The 2011 Drought/heamentioning
confidence: 99%
“…Studies on water manipulation alone (induced drought) have reported shifts in the microbial community (Berard et al, 2011). Drought induced a shift that favored fungal populations relative to bacterial populations (Bell et al, 2009) and warming treatments increased Acidobacteria and Crenarchaeota populations compared to control treatments (Sheik et al, 2011).…”
Section: Comparison Of Soil Eas During and After The 2011 Drought/heamentioning
confidence: 99%